Prescription medication-induced psychosis: A high alert for drug experts - Najla Taslim; Dustin Edge (AMMANIF, 2020)
Psychosis is a complex mental illness of behavioral, psychological, and emotional disturbances. Secondary psychosis can be elicited by prescription medications and literature is replete with examples of such drugs. Objectives: The goal of this article is to gather information from multiple published sources to highlight the culprit prescription medications that are linked with psychotic episodes and compose the findings into a simplified, standalone publication for readers to conveniently become aware of this phenomenon. It is also intended to reiterate the critical role and significance of the pharmacist as a vital player in a health care team. Methods: The scientific literature was searched on the PubMed database using the key search phrase "psychosis, medicines or drug or prescription." The search was limited to the time period from 1960-2019 to ensure the inclusion of the vast majority of previously reported cases of currently available medicines and their related psychoses. Conclusion: Commonly prescribed medications can cause serious, albeit preventable, psychiatric issues. Pharmacists as vital players in patient care can avert the untoward psychotic episode by taking timely steps in notifying the prescribers or counseling the patient on measures to avoid serious and fatal psychotic issues.